Pemetaan Informasi Sebaran Bidang Ilmu Pada Skripsi Fakultas Teknologi Pertanian Lulusan IPB University Tahun 2015-2019 Berdasarkan Standar Universal Decimal Classification: Suatu Kajian Bibliometrika - Abdul Rahman Saleh; Sri Rahayu (Perpustakaan IPB, 2020)
Introduction. Agriculture is an important sector for Indonesia. One of the agricultural sub-sectors is industry and agricultural mechanization. Progress in this field cannot be separated from research activities carried out by lecturers, researchers and students. IPB as one of the leading agricultural universities has certainly produced a lot of research in its field. To find out and photograph the research conducted by undergraduate students, this research was conducted. Methods and Data Collection. The sample is limited to the thesis of the last 5 years (2015-2019) which is taken from the IPB repository. Data analysis. Mapping is reviewed based on the UDC Classification. The table was analyzed descriptively and mapped using VosViewer. Results and Discussion. The number of thesis researches of the Faculty of Agricultural Technology, IPB during 2015-2019 is 2,055 titles. The most researched topics were “production and preservation of solid food” totaling 461 studies and the least were “ventilation and air conditioning” and “rubber industry” with only 2 studies each. The most common keyword is